Performance of the supply chains for New Zealand prefabricated house-building. (January 2021) - Masood, Rehan; Lim, James B.P.; González, Vicente A.
Highlights: Performance critical factors for prefabricated house-building companies (suppliers) were identified through expert survey. Rankings of critical factors, based on the significance, were determined through questionnaire survey. Comparative analysis was performed based on supply chain roles, experience, prefabrication technology (material and product). Comparison to leading OECD countries in prefabricated house building was performed. Theoretical and managerial implications were derived from the key findings. Abstract: Prefabrication and off-site construction offer potential solutions for housing sustainability and affordability issues. Prefabricated house-building is an emergent industry with unique supply chains to housing projects. The performance of companies in prefabricated house-building, as suppliers, is gaining importance because of the supplier-driven nature of the industry. A survey was conducted with New Zealand prefab experts, affiliated with relevant disciplines, to identify the critical challenges which impact the performance of prefabricated house-building companies. An industry-wide survey was conducted with prefabricated house-building companies to validate and establish the importance of these challenges. Nineteen factors were identified and were further classified under six performance dimensions. Most critical challenges were associated with cost and quality, while fewer related to delivery and flexibility aspects. Challenges related to features and flexibility were not considered to be of high importance. The main differences among performance challenges regarding company characteristics were found in prefabrication strategy by-products and supply chain roles. However, prefabrication strategy by-material, had far fewer differences. The findings of this paper are helpful to formalise strategic goals at organizational level, developing roadmap at the industry level, and defining policies and programmes at government level with focus on the sustainable construction of houses.